Comparative study on knowledge and practice of family planning methods among married Chepang and Brahmin/Chhetri men in Korak VDC of Chitwan district - Lama, L D; Bharati, M; Bharati, L (Journal of Chitwan Medical College, 2017)
The purpose of this study was to compare knowledge and practice of family planning methods among Chepang and Brahmin/ Chhetri men. Chepang are more disadvantage ethnicity of Nepal therefore by examine the knowledge and practice of family planning in these two groups it will be helpful to find out whether or not family planning program has been reach to un-reach group. Data were collected from the 1st Jestha 2070 to 31 Jestha 2070 (15.5.2013 to 14.6.2013) through interview methods. The average age group of both the respondents was between 26-35yrs. Majority of respondents had knowledge about both temporary and permanent (56.8 percent Chepang and 50.9 percent Brahmin/Chhetri). While most of the family planning information was obtained through a health worker (88.2 percent Chepang and 79.4 percent Brahmin/Chhetri). Family planning using was 42.1 percent in Chepang and 40.2 percent in Brahmin/Chhetri. Temporary family planning method was found to be commonly used (74.4 percent Chepang and 73.1 percent Brahmin/Chhetri). Spousal communication seemed to exist by two third portions in both the groups and the most common topic for discussion was about family and family size.